2013
DOI: 10.3390/brainsci3031109
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Regulation of CNS Inflammation and Remyelination

Abstract: Astrocytes regulate fundamentally important functions to maintain central nervous system (CNS) homeostasis. Altered astrocytic function is now recognized as a primary contributing factor to an increasing number of neurological diseases. In this review, we provide an overview of our rapidly developing understanding of the basal and inflammatory functions of astrocytes as mediators of CNS responsiveness to inflammation and injury. Specifically, we elaborate on ways that astrocytes actively participate in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 104 publications
0
54
0
Order By: Relevance
“…To date, little is known about the role of astrocytes in Krabbe disease, where the majority of studies have mainly been focused on the role oligodendrocytes in this illness. Altered astrocytic function has gained recognition as a major contributing factor to a growing number of neurological disorders (Claycomb et al, 2013) and the belief that astrocytic dysfunction significantly contributes to the development of inflammation in the CNS has gained traction in the past number of years (Sharma et al, 2010). In addition, the immunomodulatory functions of astrocytes are now being shown to actively participate in the pathogenesis of a number of demyelinating disorders (Sharma et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, little is known about the role of astrocytes in Krabbe disease, where the majority of studies have mainly been focused on the role oligodendrocytes in this illness. Altered astrocytic function has gained recognition as a major contributing factor to a growing number of neurological disorders (Claycomb et al, 2013) and the belief that astrocytic dysfunction significantly contributes to the development of inflammation in the CNS has gained traction in the past number of years (Sharma et al, 2010). In addition, the immunomodulatory functions of astrocytes are now being shown to actively participate in the pathogenesis of a number of demyelinating disorders (Sharma et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that demyelination in Krabbe disease may not be solely attributed to oligodendrocyte dysfunction and that given correct environmental support these twi/twi oligodendrocytes may function normally. Thus, astrocytic reactivity in Krabbe disease may not represent a secondary response to demyelination, but may possibly be a primary response to psychosine and in turn astrocytes may significantly contribute to the pathogenesis of Krabbe disease (Claycomb et al, 2013). In our current study, we obtained data that demonstrated a direct effect of psychosine on astrocyte cell death and attenuation by pFTY720.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated astrocytes proliferate and produce a variety of inflammatory mediators such as nitric oxide (NO), TNF-a, etc. that contribute to the pathogenesis of various neurodegenerative diseases (Sofroniew and Vinters 2010;Claycomb et al 2013). Although there are reports indicating NO-mediated apoptosis of astrocytes in rat primary astrocyte culture exposed to a combination of LPS and inflammatory cytokines but not by either alone (Suk et al 2001;Caruso et al 2007;Quintas et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Like other chronic pain conditions, spinal astrocytes are activated for at least 14 days after painful facet stretch. 16,17 Mechanical injury to the facet capsule also regulates the production of inflammatory mediators, including proinflammatory cytokines and neurotrophins, in the facet joint itself, as well as in the DRG. 46,48,53,69 Because peripheral inflammation increases hyperexcitability and substance P in DRG neurons, along with pain production, 96,110 recent studies have begun to elucidate the molecular mechanisms by which peripheral inflammation contributes to central sensitization in the context of facet-mediated pain.…”
Section: Neuronal Responses To Excessive Stretchmentioning
confidence: 99%